A Report on the Arctic College Interpreter-Translators Program - Semsch, Marlene (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1993)
AbstractThis report briefly outlines the historical developments of interpreter I translator training in the Northwest Territories. It describes the origins of the present Arctic College I IT programs at the Thebacha Campus in Fort Smith and Nunatta Campus in Iqaluit and describes their similarities and differences. It outlines admission requirements and course offerings and discusses some of the challenges faced in training aboriginal translators and interpreters.